Impact of surgery on rehabilitation care and quality of life perceived by patient with post-stroke upper limb spasticity: Study protocol for a randomized controlled trial - Patricia Hurtado-Olmo; Ángela González-Santos; Laura del Olmo Iruela; Belén Castro-Ropero; Lourdes Zúñiga-Gómez; Ana Isabel Bueno-García; Pilar Guijosa-Campos; Basilio Gómez-Pozo; Fidel Hita-Contreras; Pedro Hernández-Cortés (PLoS ONE, 2025)
Background Stroke is the principal cause of permanent disability in adult age, and many patients require lifelong medical treatment and care from others for their daily activities. It has enormous repercussions on the work and social lives of patients and their families and involves major economic expenditure. Post-stroke spastic upper limb is usually treated with rehabilitation, occupational therapy, and periodical injections of botulinum toxin, while surgical correction is now seldom considered. However, there has been no clinical trial to compare between surgical and toxin treatments. The primary aim of this study is to compare outcomes between surgery and a conventional approach with botulinum toxin in patients with post-stroke upper limb spasticity. Methods A two-arm (surgical treatment [n = 22] vs. botulinum toxin [n = 22]) randomized clinical trial (RCT) will be performed to compare the efficacy of surgery with that of botulinum toxin treatment in patients with post-stroke upper limb spasticity. Data will be collected at baseline and at 6 and 12 months of follow-up on functionality, hygienic status, quality of life, sleep quality, anxiety/depression levels, and functional magnetic resonance imaging (fMRI)-measured brain activity. Healthcare and care costs will be compared between the groups. Discussion This research is set in the context of chronic diseases, aging, and functional/mobility limitations. The results can be expected to have a major impact, because the high prevalence of stroke and the severe associated disability means that an enormous number of patients can benefit from improved treatment protocols, and a more rational use of resources would yield considerable economic benefits for health and care systems. Our expectation is that outcomes would be more favorable with surgery. However, the aim is not to exclude any approach but rather to explore how the potential and indications of each treatment could be integrated within a multidisciplinary therapeutic protocol in a complementary manner. Trial Registration: ClinicalTrials.gov (NCT06392633). Registered on 30 April 2024.